Analysis of Coupling Gear on Roller Press Cement Mill - Sulaeman; Rozi Saferi; Ropi Apriadi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2022)
This study aims to determine the causes of failure in the coupling gear, reduce or minimize damage that occurs in the coupling gear, determine the hardness of the coupling gear material, and to determine the level of wear and tear on the coupling gear. This research was conducted from July to October 2022, at PT. Semen Padang, ITP Mechanical Engineering Laboratory, FT-Unand Mechanical Engineering Metallurgical Laboratory. The test procedures used in this study are first to identify the damage, hardness testing on the coupling gear, wear testing on the coupling gear. After observing, the types of damage to the coupling gear are obtained, namely in the form of wear. The types of wear and tear on the coupling gear are scoring, plastic flow, and pitting. Based on the results of the hardness test on the first specimen, the average hardness was 41.1 HRC and on the second specimen, the hardness average was 33.5 HRC and on the third specimen, the hardness average was 34.9 HRC. The specimen that has the highest average hardness value is the first specimen with an average hardness of 41.3 HRC. the wear level in test 1 is 0.008 and in test 2 the wear level is 0.004 and in test 3 the wear level is 0.004 and in test 4 the wear level is 0.004 and in test 5 the wear level is 0.004. From the wear test it was found that the type of wear on the coupling gear material is classified as abrasive and fatigue wear because the two materials are rubbing against each other and the eroded material does not stick to each other and there is also fatigue due to the load that is applied continuously so that the material or coupling gear is worn out.